Effectiveness of Public Communication Management: Implementation of Presidential Instruction Number 9 of 2015 in the Banjarmasin City Information Communication and Statistics Service - Junaidy, Junaidy; Subhan, Rizky; Akhmad, Beni; Sauqi, Ahmad; Oktaviani DA, Elisa (Journal of Governance and Social Policy, 2024)
This research is intended to determine the management of public communications based on Presidential Instruction Number 9 of 2015 in the Banjarmasin City Communication, Information and Statistics Service. The method used is descriptive qualitative, data obtained through interviews and observation. The research results show that public communication management is carried out through three channels: above the line (print and online media publications, as well as electronic media), below the line (coordination between institutions, socialization of government activities, and exhibitions), and through the line (media publications social). Policy implementation is based on the four factors of George Edward III's implementation theory, namely communication (by policy makers, the public, and media/journalists), resources (constraints on human resources, finance, and equipment), disposition (employee understanding, implementer commitment, and incentives), as well as bureaucratic structure (SOP and clear division of work, as well as good coordination).